2010
DOI: 10.3113/fai.2010.1064
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Replacement Outcome in Low Volume Centers: Short-Term Followup

Abstract: This study demonstrated that functional results of total ankle replacement in low volume centers were comparable to most high volume centers but survival was lower especially when we consider our shorter followup than most comparable series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In contrast, data that excluded these individuals had an incidence of revision of 2.8% (19 of 692) for the Salto Ò mobile version and 2.0% (2 of 98) for the Salto TalarisÔ total ankle (Table) prostheses (20,24,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, data that excluded these individuals had an incidence of revision of 2.8% (19 of 692) for the Salto Ò mobile version and 2.0% (2 of 98) for the Salto TalarisÔ total ankle (Table) prostheses (20,24,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 77%
“…The search for potentially eligible information for inclusion in the systematic review yielded a total of 92 references that underwent (Table) (20,24,(31)(32)(33)35,36,(38)(39)(40)(41). Overlapping patients were evident for 3 data sets involving the inventors (31)(32)(33), registry data (37,38), and independent surgeons (40,41).…”
Section: Resultsmentioning
confidence: 99%
“…Following review nine of these papers were discarded for the following reasons: three were duplicates [3,8,13], two were editorials, one looked at the effect of physician owned hospitals on general competing hospitals, one looked at rural hospitals, one was a letter to the editor and one paper focused on Medicaid status. This left 21 papers of which nine were related to the knee [16][17][18][19][20][21][22][23][24], often as a more general assessment of the effect of volume on lower limb arthroplasty, and 12 looking at other aspects of orthopaedic practice [25][26][27][28][29][30][31][32][33][34][35][36]. An additional two papers [37,38] were also identified through a review of the bibliographies of identified papers.…”
Section: Methodsmentioning
confidence: 99%
“…This of course may reflect the tertiary nature of many high volume centres. Reuver et al [25] found that functional results, assessed using Standardized American Orthopaedic Foot and Ankle Society (AOFAS) scores, range of movement and satisfaction following total ankle replacement were comparable regardless of volume [25].…”
Section: Other Orthopaedic Proceduresmentioning
confidence: 99%
“…Success after TAA, however, depends heavily on surgeon experience [3][4][5][6][7] and it is difficult to gain expertise in each of the growing number of prostheses. Many of the best outcomes are reported by surgeons involved at least in the initial design of the implants under study.…”
mentioning
confidence: 99%